Augmented Reality for Student Learning Media: A Bibliometric Analysis and Visualization - Singgih Subiyantoro; Baskoro Hadi; Eka Budhi Santosa; Oka Irmade; Fatma Sukmawati (Indonesian Journal of Instructional Media and Model, 2021)
Augmented Reality is a study that is now popular. Many researches theme have been published in various reputable journals. The purpose of this study is to provide an overview and visualization of Augmented Reality which is used as a medium of learning. This research is a qualitative research through descriptive analysis with literature review formed in bibliometric analysis which describes and visualizes ongoing phenomena as well as in the past regarding various topics related to Augmented Reality. Through the Scopus database source, there are 882 documents related to Augmented Reality were obtained from 2016 to 2020 and various data related to the number of documents by country, author, subject area, visualization of relationships between topics. Topics that are categorized as rare or have not been associated with AR will be an option for us to study more deeply so that it will give knowledge to the scientific of AR as a medium for student learning.